Bcl3 phosphorylation by Akt, Erk2 and IKK is required for its transcriptional activity - Wang, Vivien Ya-Fan (Mol Cell, 2017)
Unlike prototypical IκB proteins which are inhibitors of NF-κB RelA, cRel, and RelB dimers; the atypical IκB protein Bcl3 is primarily a transcriptional coregulator of p52 and p50 homodimers. Bcl3 exists as phospho-protein in many cancer cells. Unphosphorylated Bcl3 acts as classical IκB-like inhibitor, removes p50 and p52 from bound DNA. Neither the phosphorylation site(s) nor the kinase(s) phosphorylating Bcl3 are known. Here we show Akt, Erk2, and IKK1/2 phosphorylate Bcl3. Phosphorylation of Ser33 by Akt induces switching of K48- to K63-ubiquitination; thus promotes nuclear localization and stabilization of Bcl3. Phosphorylation by Erk2 and IKK1/2 of Ser114 and Ser446 convert Bcl3 into a transcriptional coregulator by facilitating its recruitment to DNA. Cells expressing S114A/S446A mutant have cellular proliferation and migration defects. This work links Akt and MAPK pathways to NF-κB through Bcl3 and provides mechanistic insight into how Bcl3 functions as an oncoprotein through collaboration with IKK1/2, Akt, and Erk2.